Hubungan Pengetahuan dengan Sikap SADARI (Pemeriksaan Payudara Sendiri) pada Remaja Putri: The Correlation between Knowledge and Attitudes Young Women about Breast Self-Examination (BSE) - Windayanti, Hapsari; Widayati (Universitas Ngudi waluyo, 2023)
The number of breast cancer cases is ranked second after cervical cancer, the most common among women in the world. A survey conducted by WHO stated that 8-9% of women suffer from breast cancer. Breast self-examination is very important because almost 85% of breast lumps are discovered by sufferers themselves. This method is very simple, but it is hoped that it can reduce the high number of breast cancer sufferers, because the earlier it is detected, the faster the treatment process is needed. BSE is an important thing for teenagers to know to help teenagers carry out early detection of breast cancer. Good knowledge about BSE can help teenagers have a positive attitude towards themselves. The aim of the research is to determine the relationship between knowledge and BSE attitudes in young women. The population of female students at SMK